Impact of Platelet Glycoprotein Ia/IIa C807T Gene Polymorphisms on Coronary Artery Aneurysms of KD Patients. (24th February 2021) - Li, Wei; Pi, Lei; Yuan, Jia; Gu, Xueping; Wang, Zhouping; Liu, Yunfeng; Deng, Qiulian; Wang, Yanfei; Huang, Ping; Zhang, Li; Gu, Xiaoqiong
Abstract : Background . Kawasaki disease (KD) is a systemic vasculitis of unknown etiology in children. Coronary artery abnormalities are the most common complications of KD. Recent evidence showed that genetic polymorphisms may lead to susceptibility to KD. Genetic variants in platelet glycoprotein have been reported to be associated with coronary artery disease. The aim of the present study is to investigate the correlation between the role of platelet glycoprotein and coronary artery aneurysms in KD patients. Methods . We did a case-control study that enrolled 818 KD patients and 1401 healthy children with the same age and sex from January 2013 to December 2016. Analysis of single-nucleotide polymorphism (rs1126643) of the platelet glycoprotein Ia/IIa C807T was performed by multiplex polymerase chain reactions in this study. Results . A significant difference in the genotype distribution between KD cases and controls was observed for the glycoprotein Ia/IIa C807T (rs1126643) polymorphism (p = 0.026 ). Compared with the healthy children, the rs1126643T allele carriers had odds ratio (OR) of 0.63 for developing KD (TT vs. CC: adjusted OR = 0.62, 95% confidence interval (CI) = 0.43–0.88, p = 0.0078 ; TT vs. CT/CC: adjusted OR = 0.63, 95% CI = 0.44–0.889, p = 0.0093 ). Furthermore, we also found that children less than 60 months of age and female patients with rs1126643 T allele carriers had an adjusted OR of 0.66 (95% CI = 0.46–0.95) for noncoronary artery aneurysm patients (p = 0.0242 ). Single-nucleotide polymorphism rs1126643 TT seems to represent a protective factor against KD in coronary artery aneurysm formation in multivariate analysis. Conclusions . The platelet glycoprotein Ia/IIa T allele carriers may have a protective effect on the risk of coronary artery aneurysms of KD patients, especially in females and children aged less than 60 months. These results may provide evidence for platelet glycoprotein Ia/IIa gene polymorphisms in the pathogenesis of KD patients.